Registration of 'CP 06‐2042' Sugarcane. Issue 2 (27th April 2017) - Davidson, R. Wayne; Sandhu, Hardev S.; McCord, Per; Comstock, Jack C.; Edmé, Serge J.; Zhao, Duli; Glaz, Barry; Sood, Sushma; Glynn, Neil C.; Gilbert, Robert A.; Singh, Maninder P.; Baltazar, Miguel; et al.
Abstract : 'CP 06‐2042' (Reg. No. CV‐169, PI 675156) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugarcane League and released to growers for organic (muck) and mineral (sand) soils in Florida in September 2014. CP 06‐2042 was selected from a cross of 'CP 96‐1252' × 01 P 04 made at Canal Point, FL, in December 2001. The female parent, CP 96‐1252, is a commercial cultivar. The male parent is unknown, as it is one of 19 sugarcane cultivars in the polycross. Cane yield of CP 06‐2042 on muck soils, averaged across 18 harvests through three crop cycles (plant cane, first ratoon, and second ratoon), was 26.1% higher ( P < 0.1) than that of 'CP 89‐2143', a commercial check for muck soils. Although CP 06‐2042 had 1.8% lower commercial recoverable sucrose than CP 89‐2143, high cane yield resulted in 22.8% higher ( P < 0.1) sucrose yield than CP 89‐2143. Averaged across nine harvests through three crop cycles on sand soils, CP 06‐2042 had 12.1% ( P < 0.1) higher cane yield, 2.9% higher commercial recoverable sucrose, and 13.1% ( P < 0.1) higher sucrose yield than 'CP 78‐1628', a commercial check for sand soils. CP 06‐2042 was released because of its high cane and sucrose yields on both muck and sand soils and its acceptable levels of resistance to brown rust, leaf scald, Sugarcane mosaic virus strain E (mosaic), and ratoon stunt. CP 06‐2042 is susceptible to orange rust and has poor freeze tolerance.